Positive end-expiratory pressure management in patients with severe ARDS: implications of prone positioning and extracorporeal membrane oxygenation - Bösing, Christoph; Rocco, Patricia R. M.; Luecke, Thomas; Krebs, Jörg (Critical care, 2024)
The optimal strategy for positive end-expiratory pressure (PEEP) titration in the management of severe acute respiratory distress syndrome (ARDS) patients remains unclear. Current guidelines emphasize the importance of a careful risk-benefit assessment for PEEP titration in terms of cardiopulmonary function in these patients. Over the last few decades, the primary goal of PEEP usage has shifted from merely improving oxygenation to emphasizing lung protection, with a growing focus on the individual pattern of lung injury, lung and chest wall mechanics, and the hemodynamic consequences of PEEP. In moderate-to-severe ARDS patients, prone positioning (PP) is recommended as part of a lung protective ventilation strategy to reduce mortality. However, the physiologic changes in respiratory mechanics and hemodynamics during PP may require careful re-assessment of the ventilation strategy, including PEEP. For the most severe ARDS patients with refractory gas exchange impairment, where lung protective ventilation is not possible, veno-venous extracorporeal membrane oxygenation (V-V ECMO) facilitates gas exchange and allows for a “lung rest” strategy using “ultraprotective” ventilation. Consequently, the importance of lung recruitment to improve oxygenation and homogenize ventilation with adequate PEEP may differ in severe ARDS patients treated with V-V ECMO compared to those managed conservatively. This review discusses PEEP management in severe ARDS patients and the implications of management with PP or V-V ECMO with respect to respiratory mechanics and hemodynamic function.